Original paperEffects of folic acid on dyslipidemia and serum homocysteine in a rat model of cholestasis and hepatic fibrosis - Mohammadian, Zahra; Eidi, Akram; Mortazavi, Pejman; Tavangar, Seyed Mohammad; Asghari, Ahmad (Polish Journal of Pathology, 2015)
The liver is the major site for storage and metabolism of folate. Folate deficiency is common in many liver diseases and causes severe effects on cellular metabolism and increases oxidative stress and the homocysteine (Hcy) level. The objective of this research was to investigate the effects of folic acid on dyslipidemia and serum Hcy concentrations in an experimental rat model of cholestasis. Eighty-one male Wistar rats were divided into nine groups: control, sham-operated, folic acid control, bile duct-ligated (BDL), and BDL+ folic acid groups. In folic acid treated groups, folic acid (1, 5, and 10 mg/kg body weight) was given orally for 28 days. After taking blood and liver samples, plasma lipid profiles and Hcy and hepatic reduced and oxidized glutathione concentrations were measured. Histopathological features of cholestasis were assessed by Masson’s trichrome staining. Treatment of folic acid in BDL rats significantly prevented the progression of hepatic fibrosis and improved the serum and liver biochemical changes. These results suggest that folic acid protects the liver against cholestasis by reducing serum Hcy and by its antioxidant properties. Folic acid can be an important therapeutic intervention in dyslipidemia caused by cholestasis.